2002
DOI: 10.1177/0013161x02381003
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Professional Community: Tales from Two High Schools

Abstract: This comparative case study of two urban high schools surfaced a critical paradox of professional community heretofore obscured in the literature. Although extant literature has focused on school structures, values, and beliefs that engender collective identity, this study brings into focus the importance of both professional autonomy (“I-ness”) and shared identity (“we-ness”) in professional community. Examining the findings through two lenses—professional community and micropolitics—this study explores how, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 15 publications
1
28
0
2
Order By: Relevance
“…In other words, teachers who are respected for their expertise take a higher level of responsibility towards student learning and collaborate with other teachers in this respect. In an environment where there is trust in administrator, schools become professional learning communities (Scribner et al, 2002). Working together, playing an active role in decisionmaking processes, and applying democracy within the school facilitate the implementation of distributed leadership (Oduro, 2004).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…In other words, teachers who are respected for their expertise take a higher level of responsibility towards student learning and collaborate with other teachers in this respect. In an environment where there is trust in administrator, schools become professional learning communities (Scribner et al, 2002). Working together, playing an active role in decisionmaking processes, and applying democracy within the school facilitate the implementation of distributed leadership (Oduro, 2004).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Furthermore, it is shown that autonomous motivation often leads to "meaningful collegial contacts" (Clement and Vandenberghe, 2000, p. 91). Scribner et al (2002) demonstrate that professional autonomy does not imply that teachers define their practice in isolation or that the autonomy that teachers seek to have in their work impedes them from collaborating. They further argue that the "degree of professional autonomy that principals provide teachers can be directly related to the strength of professional community" (Scribner et al, 2002, p. 70).…”
Section: Teacher Autonomymentioning
confidence: 94%
“…Different meanings and understandings of teacher collaboration also find their expression in various terms used to describe the phenomenon. The literature on teacher collaboration draws on many different expressions, such as teacher teams (e.g., Pounder, 1999), professional communities (e.g., Coburn and Russel, 2008;Thoonen et al, 2011), professional learning communities (e.g., Scribner et al, 2002;Vescio et al, 2008), or communities of practice (e.g., Hew and Hara, 2007;Goodnough et al, 2009).…”
Section: Collaboration As a Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…Even authors that focused on other denominations often seemed to use the term "team" somewhere in their article: some studies started off by writing about "collaboration", "community", "department" or "critical friends group" and then later on referred to "teams" (mostly as a form of collaboration) without giving further explanation (e.g. Achinstein, 2002;Avila De Lima, 2001;Curry, 2008;Datnow, 2011;Dickinson, 2009;Kelchtermans, 2006;Leonard & Leonard, 2003;Lomos, Hofman, & Bosker, 2011;Scribner, Hager, & Warne, 2002;Visscher & Witziers, 2004;Williams, 2010). This mix up of different terms is confirmed by Westheimer (2008) who mentioned that schools use different denominations to describe collaboration between teachers, one of them being "teams".…”
Section: On the Use Of The Term 'Team'mentioning
confidence: 99%